Western Mexico seismic source model for the seismic hazard assessment of the Jalisco-Colima-Michoacan region - Sawires, Rashad; Santoyo, Miguel A.; Peláez, José A; Henares, Jesús (Natural Hazards, 2021)
The Mexican subduction zone, the Gulf of California spreading center, as well as the triple junction point around the Jalisco and the Michoacan Blocks, represents the most active seismogenic belts inducing seismic hazard in the Jalisco-Colima-Michoacan region. Herein, considering such seismotectonic setting, we develop a new seismic source model for the surrounding of Jalisco-Colima-Michoacan to be used as an input in the assessment of the seismic hazard of the region. This new model is based on revised Poissonian earthquake (1787-2018) and focal mechanism (1963-2015) catalogs, as well as crustal thickness data and all information about the geometry of the subducting slabs. The proposed model consists of a total of 37 area sources, comprising all the three different possible categories of seismicity: shallow crustal, interface subduction, and inslab earthquakes. A special care was taken during the delimitation of the boundaries for each area source to ensure that they represent a relatively homogeneous seismotectonic region and to include a relatively large number of earthquakes that enable us to compute as reliable as possible seismicity parameters. Although the sources were delimited following the standard criteria of assessing the probabilistic seismic hazard, they are also characterized in terms of their seismicity parameters (annual rate of earthquakes above Mw 4.0, b-value, and maximum expected magnitude), mean seismogenic depth, as well as the predominant stress regime. The proposed model defines and characterizes regionalized potential seismic sources that can contribute to the seismic hazard at the Jalisco-Colima-Michoacan region, providing the necessary information for seismic hazard estimates.
Keywords: seismic sources; seismicity parameters; earthquakes; stress regime; Jalisco-Colima-Michoacá n region; Western Mexico; JCR; Scopus